1999
DOI: 10.1021/jm980428x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Evaluation, and Comparative Molecular Field Analysis of 1-Phenyl-3-amino-1,2,3,4-tetrahydronaphthalenes as Ligands for Histamine H1 Receptors

Abstract: A series of 1-phenyl-3-amino-1,2,3,4-tetrahydronaphthalenes (1-phenyl-3-aminotetralins, PATs) previously was found to modulate tyrosine hydroxylase activity and dopamine synthesis in rodent forebrain through interaction with a binding site labeled by [(3)H]-(-)-(1R,3S)-trans-H(2)-PAT. Recently, we have discovered that PATs also bind with high affinity to the [(3)H]mepyramine-labeled H(1) receptor in rat and guinea pig brain. Here, we report the synthesis and biological evaluation of additional PAT analogues in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 20 publications
2
44
1
Order By: Relevance
“…Our studies show that the histamine H 1 receptor is constitutively expressed as both monomeric and multimeric entities. Moreover, as previously suggested (Booth et al, , 2002Bucholtz et al, 1999;Choksi et al, 2000), our studies indicate that the recently introduced H 1 receptor radioligand…”
supporting
confidence: 84%
“…Our studies show that the histamine H 1 receptor is constitutively expressed as both monomeric and multimeric entities. Moreover, as previously suggested (Booth et al, , 2002Bucholtz et al, 1999;Choksi et al, 2000), our studies indicate that the recently introduced H 1 receptor radioligand…”
supporting
confidence: 84%
“…For example, a-adrenergic receptors may modulate activity of the 5-HT2 circuitry or be direct targets of DOI (Darmani, 1993;Ray, 2010). Relevant here is that an early (1993) NovaScreen of racemic 6-OH-7-Cl-PAT reported appreciable (K i ∌70 nM) at rat brain a 1 -adrenergic receptors yet negligible affinity for all other aminergic neurotransmitter receptors and two dozen other central nervous system receptor sites, with the known exceptions of histamine H 1 (Bucholtz et al, 1999) and 5-HT2 receptors. Pharmacological studies are under way to assess the role of specific a 1 -adrenergic receptor subtypes in regulating the DOI-elicited HTR, and molecular modeling studies are in progress to assess interactions between 6-OH-7-Cl-PAT enantiomers and a 1 -adrenergic receptor TMD amino acids.…”
Section: Discussionmentioning
confidence: 76%
“…The PATs were synthesized in our laboratory as racemic mixtures. Single enantiomers were resolved by chiral stationary-phase high-performance liquid chromatography and converted to hydrochloride salts as previously described (Bucholtz et al, 1999;Booth et al, 2009;Vincek and Booth, 2009 …”
Section: Compoundsmentioning
confidence: 99%
“…[6] The evolution of this concept has been pursued for privileged structures associated with a target receptor family [1d] (e.g., 5,5-transfused lactams for serine protease, reverse turn mimic for G protein-coupled receptor). However, Schnur et al [7] refute the so-called target family privileged structures having analyzed target family ligands in the MDDR database which contains compounds targeted and tested for potential therapeutic value that were compiled from literature data and confirm even more the definition of the original concept of privileged structures by Evans et al [2] The 1-aryltetralin system 1 is a privileged structure found in natural cyclolignans and synthetic derivatives which present a wide range of biological activities, [8][9][10] such as the inhibition of tubulin polymerization and DNA topoisomerase II, and immunosuppressive, anti-HIV, and antidepressant activities. Recently, cyclolignans have been reported as inhibitors of the insulin-like growth factor receptor (IGF-1R).…”
Section: Introductionmentioning
confidence: 98%